Students’ Perception Towards ChatGPT for Academic Writing at English Study Program FKIP Universitas Riau - Nurul Khofifah Lubis; Fadly Azhar; Afrianto Daud (Universitas Islam Negeri Palopo, 2025)
This research is aims to find out students' perception towards ChatGPT for academic writing at English Study Program, FKIP Universitas Riau. In this research, quantitative method was used and data was collected using online questionnaire from G-form. For the sample, this research used purposive sampling technique, where 73 respondents met the criteria set by the researcher so that they were used as respondents in this research. The findings show that students have a positive perception of ChatGPT, with an overall average score of 3.73 which falls into the high category. Students responded positively to the ease of using ChatGPT, improving the quality of academic writing, improving students' writing skills, helping in finding ideas or finding additional references quickly, improving grammar, helping to paraphrase so that overall, it can be said that ChatGPT is useful for students who help them in the academic writing process. However, there are some students who are still hesitant to use ChatGPT in the long run. This hesitation may be due to concerns related to the impact caused by its use such as the emergence of dependency, and the accuracy of answers that are sometimes less precise or misleading. To address this, students are advised to use ChatGPT by not rely entirely on this tool. They still need to verify information and combine it with credible academic sources.